2022
DOI: 10.1039/d2md00116k
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine tethered bergenin heterocyclic hybrids: design, synthesis, anticancer activity, and molecular docking studies

Abstract: Novel piperazine-linked bergenin derivatives were synthesized and the compounds 5a, 5c, 10f, and 13o showed excellent cytotoxic activity. These compounds arrest the cell cycle and induce apoptosis by regulating the Bax/BcL2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Targeting ubiquitination of Mcl-1 is allowed for rapidly eliminating proteins and triggering cell death while responding to various cellular events [ 37 ]. Environmental cadmium exposure leads to placental apoptosis and fetal growth restriction through Parkin-induced degradation of Mcl-1 ubiquitination during gestation [ 38 ]. Inhibition of BMI-1 also leads to DUB3-dependent Mcl-1 degradation, resulting in enhanced apoptosis of cancer cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting ubiquitination of Mcl-1 is allowed for rapidly eliminating proteins and triggering cell death while responding to various cellular events [ 37 ]. Environmental cadmium exposure leads to placental apoptosis and fetal growth restriction through Parkin-induced degradation of Mcl-1 ubiquitination during gestation [ 38 ]. Inhibition of BMI-1 also leads to DUB3-dependent Mcl-1 degradation, resulting in enhanced apoptosis of cancer cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…But other protein targets are implicated in the mechanism of action. Previous studies also suggested the binding of bergenin to the proteins NLRP3 (NOD-like receptor family-pyrin domain containing 3) inflammasome [129], antiapoptotic protein B-Cell Lymphoma 2 (Bcl-2) [130], enzyme galectin-3 [131] and several other proteins [132][133][134][135].…”
Section: Polyphenols and Flavonoidsmentioning
confidence: 94%
“…Annexin V-FITC apoptosis detection kit was used to determine the effect of compounds on CAL-27 cells as described previously (Venkateswara Rao et al 2022). Initially, the CAL-27 cells in the density of 5×10 3 cells were seeded in 6-well plate and incubated for overnight at 37 °C in 5% CO 2 .…”
Section: Apoptosis Analysismentioning
confidence: 99%